Design and Implementation of 5 kWSmart DC Microgrid - Chinmaya, H. G.; Balachandra, T. C. (Asian Journal of Electrical Sciences, 2019)
This paper presents a design for electrification of a remote village with the help of locally generated renewable electricity from solar PV modules. The whole system setup works on DC. Regulated DC bus is efficiently used to power up DC fans, DC lights in the houses of the selected village. Remote Monitoring System is used in order to continuously monitor the power plant and control the power plant. The main reason to go for DC microgrid rather than AC grid is to avoid the problem of losses and power factor. A 5 kW DC microgrid consisting of a 5-kW solar PV array and a 96V, 200Ah battery bank is developed. The system is simulated in MATLAB for a variety of operating conditions and results are presented.